RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDE, DENTAL CARE AND DENTAL CARIES IN CHILDREN - Rona Sari Putri; Susmini Susmini (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2018)
Tooth decay is a health problem that strikes the world and many are found in children around the world. Dental caries is caused by the lack of dental care in children. This study aims to determine the relationship between knowledge, attitude, dental care with child dental caries. This research merupalan koreasional research with cross sectional approach. The population is all school children aged 7-12 years some 59 people in Eleos Foundation Sukodadi Village Wagir District Malang Regency, with sampling using total samples. Variables bebeas is knowledge, attitude, and dental maintenance, while the dependent variable is dental caries. Instrument using questionnaires sheet and observation sheet. Data analysis using spearman rank test. The result of this research is got half of respondents have good knowledge, almost half of respondents have enough attitude, and hamipr all respondents have less dental maintenance action. The statistic test concluded that there is no correlation between knowledge, attitude, dental care with dental caries of children aged 7-12 years in Eleos Indonesia Foundation Sukodadi Village Wagir Sub-district, Malang Regency. It is recommended for the next researcher to increase the supporting variable that cause dental caries.Â Â